2022
DOI: 10.3390/tropicalmed7110343
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Antidiabetic Drugs on Tuberculosis Risk and Treatment Outcomes: Systematic Review and Meta-Analysis

Abstract: Tuberculosis and diabetes mellitus are two global pandemics and rising public health problems. Recent studies suggest that oral antidiabetic drugs (OADs) could reduce the risk of tuberculosis and improve clinical outcomes. However, the evidence is controversial. Therefore, we aimed to assess the effect of OADs on the risk of tuberculosis and treatment outcomes. We systematically searched for six databases from inception to 31 August 2022. We followed a predefined PICO/PECO strategy and included two randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…There is recent evidence that CCBs, beta-blockers, statins, and oral antidiabetics could act as immunomodulators—by improving the host’s anti-mycobacterial responses—and optimize the effect of anti-tuberculosis drugs or reducing the risk of developing active tuberculosis ( Kristiansen and Amaral, 1997 ; Gupta et al, 2009 ; Gupta et al, 2013 ; Meregildo-Rodriguez et al, 2022a ; Meregildo-Rodriguez et al, 2022b ), which is consistent with our results. Conversely, one systematic review and meta-analysis has reported that some oral antidiabetic drugs, such as DPP-4 inhibitors, could increase the risk of developing tuberculosis in patients with diabetes ( Meregildo-Rodriguez et al, 2022b ).…”
Section: Discussionsupporting
confidence: 92%
“…There is recent evidence that CCBs, beta-blockers, statins, and oral antidiabetics could act as immunomodulators—by improving the host’s anti-mycobacterial responses—and optimize the effect of anti-tuberculosis drugs or reducing the risk of developing active tuberculosis ( Kristiansen and Amaral, 1997 ; Gupta et al, 2009 ; Gupta et al, 2013 ; Meregildo-Rodriguez et al, 2022a ; Meregildo-Rodriguez et al, 2022b ), which is consistent with our results. Conversely, one systematic review and meta-analysis has reported that some oral antidiabetic drugs, such as DPP-4 inhibitors, could increase the risk of developing tuberculosis in patients with diabetes ( Meregildo-Rodriguez et al, 2022b ).…”
Section: Discussionsupporting
confidence: 92%
“…The endpoint of the observation was defined as the end of treatment in the survival analysis. As treatment outcome is influenced by multiple factors, we explored weight, BMI, tobacco use, alcohol use, diabetes mellitus type 2 status, albumin, cavity, baseline time to culture positivity and other factors that may be potential confounders based on the previous study ( Madzgharashvili et al, 2021 ; Meregildo-Rodriguez et al, 2022 ). The association between linezolid drug exposure and treatment outcome were adjusted by the identified covariates based on the univariate analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A recently published meta-analysis on the same topic [37], and which includes 14 studies with more than 1500 participants, is less optimistic, in that it suggests a similar sensitivity between qPCR and dPCR in pulmonary tuberculosis but recognizes a higher sensitivity for dPCR in cases of extrapulmonary tuberculosis.…”
Section: Bacteriology Applicationsmentioning
confidence: 99%